Back-To-Islam Versus Islamic Moderation Movements In Indonesia - Kastolani; Munajat; Yusof, Abdullah (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2020)
The present study to analyze the social activities of the fundamentalist movements in contrast to those of the moderate Islamic movement in Indonesia. It focusses on two groups in Salatiga Central Java: the Hati Beriman Foundation and the Khadijah Volunteer representing the fundamentalist groups, which they call themselves as the Back-to-Islam movement, and the Muhammadiyah and Nahdlatul Ulama (NU) representing the moderate groups. By observing the activities of those groups and interviewing their key activists, the study investigates their contstations and why the Back-to-Islam group has gained more popularity to te public rather than those of the moderate groups. The results show that that the emergence of Back-to-Islam movements marks a new contestation between Muslim fundamentalism and moderate Muslims in Indonesia. Previously, the contestation focused on debates around the meaning of Islamic texts or teachings, but now it moves forward to get more Muslim sympathy in general. Moreover, that transition arises because of the political defeat of Muslim fundamentalist groups in upholding Islamic law (sharia). Besides, the transition occurred because fundamentalist Muslim groups considered that Muslims in Indonesia were experiencing pressure through radical stigma and terrorism.